The contribution of adenines in the catalytic core of 10-23 DNAzyme improved by the 6-amino group modifications. Issue 18 (15th September 2016) - Zhu, Junfei; Li, Zhiwen; Wang, Qi; Liu, Yang; He, Junlin
Graphical abstract: Abstract: In the catalytic core of 10-23 DNAzyme, its five adenine residues are moderate conservative, but with highly conserved functional groups like 6-amino group and 7-nitrogen atom. It is this critical conservation that these two groups could be modified for better contribution. With 2′-deoxyadenosine analogues, several functional groups were introduced at the 6-amino group of the five adenine residues. 3-Aminopropyl substituent at 6-amino group of A15 resulted in a five-fold increase of k obs . More efficient DNAzymes are expected by delicate design of the linkage and the external functional groups for this 6-amino group of A15. With this modification approach, other functional groups or residues could be optimized for 10-23 DNAzyme.